A pilot phase II Study of digoxin in patients with recurrent prostate cancer as evident by a rising PSA - Lin, Jianqing (Am J Cancer Ther Pharmacol, 2014)
BACKGROUND: Digoxin was found to inhibit prostate cancer (PCa) growth via the inhibition of HIF-1α synthesis in a mouse model. We hypothesized that a therapeutic dose of digoxin could inhibit human PCa growth and disease progression. METHODS: An open label, single arm pilot study was performed. Patients (pts) with non-metastatic, biochemically relapsed PCa with prostate specific antigen doubling time (PSADT) of 3–24 months and no hormonal therapy within the past 6 months were enrolled. All pts had testosterone > 50 ng/dL at baseline. Digoxin was taken daily with dose titration to achieve a target therapeutic level (0.8 – 2 ng/ml); patients had routine follow-up including cardiac monitoring with 12-lead electrocardiograms (ECGs) and digoxin levels. The primary endpoint was the proportion of pts at 6 months post-treatment with a PSADT ≥ 200% from the baseline. HIF-1α downstream molecule vascular endothelial growth factor (VEGF) was measured in plasma. RESULTS: Sixteen pts were enrolled and 14 pts finished the planned 6 months of treatment. Twenty percent (3/15) of the pts had PSA decrease >25% from baseline with a medium duration of 14 months. At 6 months, 5 of 13 (38%) pts had PSADT ≥ 200% of the baseline PSADT and were continued on study for an additional 24 weeks of treatment. Two patients had durable PSA response for more than 1 year. Digoxin was well tolerated with possible relation of one grade 3 back pain. No patients had evidence of digoxin toxicity. The digoxin dose was lowered in 2 patients for significant ECGs changes (sinus bradycardia and QT prolongation), and there were probable digoxin-related ECG changes in 3 patients. Plasma VEGF was detected in 4 (25%) patients. CONCLUSIONS: Digoxin was well tolerated and showed a prolongation of PSDAT in 38% of the patients. However, there was no significant difference comparing that of similar patients on placebo from historical data. Digoxin at the dose used in this study may have limited benefit for patients with biochemically relapsed prostate cancer.